Prevalence of Dental Caries Among Smoking and Smokeless Tobacco Users Attending A Dental Hospital - Farah Shahid, Sadi Zaheer, Ahmed Mukhtar Chema, Osama Khattak, Muhammad Afzal, Waqar Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of dental caries among smoking and smokeless tobacco users attending a dental hospital. Study design: Randomized Controlled Trial. Study Setting: The study was conducted at Oral & Maxillofacial Surgery Department, Akhtar Saeed Medical & Dental College, Lahore from November 2021 to April 2022. Methods: Patients were instructed to brush their teeth and gargle with water before their examinations, after which a cotton swab was used to dry the teeth and note any instances of dental caries. We utilised an index called DMFT, where D stands for decaying teeth, M for missing teeth, F for filled teeth, and T for tooth health Results: There were 42 chewers and 42 non-chewers in the age between 20 – 60 yrs. Subjects of same age groups were selected in both the groups. 73.8% of the study subjects in both the groups were males and the remaining 26.2% were females. Results shows the distribution of the study subjects according to DMFS scores. Among the chewers, 38.1% of study subjects were caries free (DMFS = 0) and 61.9% were caries affected (DMFS = 1 or more). In the non-chewers group, 9.5% were caries free and 90.5% were caries affected. Conclusion: A greater incidence of dental caries has been linked to tobacco use. Those who smoked cigarettes had a higher DMFT score. They also had a higher caries index, which is an indicator of poor oral hygiene. Keywords: Prevalence, Dental Caries, Smokeless Tobacco Users